A congregação do Colégio Pedro II e os debates sobre o ensino de matemática - Tavares, Jane Cardote (2002)
Colégio Pedro II was criated to be a model to others country colleges, in the XIX century s first half). College teachers had a meet to discuss, vote and aprove changes: the Congregation of Colégio Pedro II. So hapenned with changes and reforms would be practice in all country classes of math. These discussions relationated with contends and metodology are analised based on Congregation meetings scripts since 1891 to 1958, and APER, the Euclides Roxo Personal Archive. Teach reforms ways can be perceived by some facts described. Congregation s president got high status by its competency and excelence. Mathematical discipline arises when Congregation in its best time. But revolucionary forces make the country insecure and convulsive. Then, revolucionary government atract education discuss disrespecting ancient traditional institutions. So, arising our Teach National System sink Congregation influence power. Could be the unified mathematic a scholar discipline, criated by decret exists in the way its criators idealized? Some teachers idiosyncrasy and workers are pointed out. So power ideas in mathematic teach evolution can be understood, in focus mathematical disciplines unifing.